Roots and routes: towards a pedagogy of worldliness - Datoo, Al Karim; Stones, Alexis (2024)
This article proposes the notion of ‘worldliness’ as a necessary companion to the Religion and Worldviews curriculum. We posit that an understanding of ‘worldliness’, grounded in empirical research, in which the individual negotiates commitments to one’s home (filial) and host (affilial) communities, is pedagogically relevant and heuristically beneficial to the lens of the worldview paradigm proposed for Religious Education (RE). We draw on the analysis and synthesis of an earlier ethnographic study, in which ‘worldliness’ was found to be a socio- and religio-cultural practice whereby diasporic youth navigate complex identities and affiliations. We argue that 1) a pedagogical approach to a worldviews curriculum calls for an understanding of ‘worldliness’ as a framework for making sense of agency in the construction of one’s own worldview; 2) ‘worldliness’ is a site for RE pedagogical exploration to counter the power imbalance of the dominant affiliative over the filial, and 3) this needs to be made explicit in RE pedagogy.
Keywords: Pedagogy; worldliness; inter-generational; Diaspora